Sifat Tanah dan Pola Curah Hujan pada Perkebunan Kayu Manis (Cinnamomum burmannii) di Mandailing Natal, Sumatera Utara: Soil Properties and Rainfall Regimes in Cinnamon (Cinnamomum burmannii) Plantations in Mandailing Natal, North Sumatra - Ritonga, Faujiah Nurhasanah; Lestari, Andi Tri; Susilowati, Arida; Pelawi, Deanova Frestiana Br; Anna, Nelly; Hartini, Kansih Sri; Elfiati, Deni (PERENNIAL, 2026)
The sustainable cultivation of Cinnamomum burmannii in tropical regions requires a thorough understanding of soil properties and rainfall patterns, as these factors critically influence nutrient availability, plant growth, and long-term productivity. This study evaluates the soil properties and climatic conditions of Sawahan Village, Mandailing Natal Regency, to assess their suitability for the cultivation of C. burmannii. Soil samples were analyzed for physical and chemical characteristics, including organic carbon, total nitrogen, phosphorus, potassium, pH, exchangeable aluminum, macro- and micronutrients, and soil texture. Rainfall data over 25 years were also examined to understand the water availability and potential influence on soil fertility. The results indicate that the soils possess moderate organic matter and nutrient content, slightly acidic to near-neutral pH, absence of exchangeable aluminum toxicity, and a sandy loam texture conducive to drainage and root growth. The region experiences high and well-distributed rainfall, which supports perennial crop development but may increase nutrient leaching in sandy soils. These findings suggest that Sawahan Village provides favorable conditions for C. burmannii cultivation, provided that sustainable soil management practices, such as organic amendments, balanced fertilization, and erosion control, are implemented. The study highlights the importance of integrating climatic and soil assessments to optimize cinnamon productivity and provides baseline data for future land management and agroforestry planning in tropical regions.